SCIENCE PROCESS SKILLS: ANALYSIS OF STUDENTS' OBSERVATIONAL ABILITY ON MATERIAL CHANGES IN SUBSTANCE FORMS - Purnama Wirayuda, Ricky (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
The research aims to determine how students' ability to observe material changes in the state of matter. This research was conducted using classroom action research methods divided into three cycles. This research was conducted at MTS Al-Hidayah Kebon IX, Sungai Gelam District, Muaro Jambi Regency. This research was conducted in the even semester of the 2022/2023 academic year. The population in this study were all students of class VII MTS Al-Hidayah Kebon IX class XI, totaling 68 students consisting of 3 classes. The sampling technique in this study used the Random Sampling technique, so the samples in this study were 23 students in class VII Nurul Bukhari and 19 students in class VII Muslim. As for the results obtained after the researchers conducted the research, it can be concluded that the students' science process skills on the indicator of observing ability were included in the good category. This was evidenced by increased students' observing abilities from cycle I to cycle III.